Do Chinese subordinates trust their German supervisors? A model of inter-cultural trust development - Bueechl, Joerg; Pudelko, Markus; Gillespie, Nicole (Journal of International Business Studies, 2023)
Abstract In this qualitative study based on 95 interviews with Chinese subordinates and their German supervisors, we inductively develop a model which advances theoretical understanding by showing how inter-cultural trust development in hierarchical relationships is the result of six distinct elements: the subordinate trustor’s cultural profile (cosmopolitans, hybrids, culturally bounds), the psychological mechanisms operating within the trustor (role expectations and cultural accommodation), and contextual moderators (e.g., country context, time spent in foreign culture, and third-party influencers), which together influence the trust forms (e.g., presumptive trust, relational trust) and trust dynamics (e.g., trust breakdown and repair) within relationship phases over time (initial contact, trust continuation, trust disillusionment, separation, and acculturation). Our findings challenge the assumption that cultural differences result in low levels of initial trust and highlight the strong role the subordinate’s cultural profile can have on the dynamics and trajectory of trust in hierarchical relationships. Our model highlights that inter-cultural trust development operates as a variform universal, following the combined universalistic-particularistic paradigm in cross-cultural management, with both culturally generalizable etic dynamics, as well as culturally specific etic manifestations.